1988
DOI: 10.1103/physreva.38.434
|View full text |Cite
|
Sign up to set email alerts
|

Study of phase-separation dynamics by use of cell dynamical systems. I. Modeling

Abstract: We present a computationally efficient scheme of modeling the phase-ordering dynamics of thermodynamically unstable phases. The scheme utilizes space-time discrete dynamical systems, viz. , cell dynamical systems (CDS). Our proposal is tantamount to proposing new Ansatze for the kinetic-level description of the dynamics. Our present exposition consists of two parts: part I (this paper) deals mainly with methodology and part II [S. Puri and Y. Oono, Phys. Rev. A (to be published)] gives detailed demonstrations.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
325
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 588 publications
(331 citation statements)
references
References 56 publications
6
325
0
Order By: Relevance
“…In analogy to pattern formation and phase separation in diblock copolymers (35,36,(47)(48)(49), a conventional CDS model approach was chosen to reproduce the experimentally observed light-induced patterns. The local concentration c is identified with the order parameter ψ of the system ðc = ψÞ.…”
Section: Methodsmentioning
confidence: 99%
“…In analogy to pattern formation and phase separation in diblock copolymers (35,36,(47)(48)(49), a conventional CDS model approach was chosen to reproduce the experimentally observed light-induced patterns. The local concentration c is identified with the order parameter ψ of the system ðc = ψÞ.…”
Section: Methodsmentioning
confidence: 99%
“…The traditional tanh mapping 29 is not used. Rather we use the mapping directly derived from the free energy functional (2)-(4), 30,31 which is essential for studying the subtle nature of nucleation and growth when one phase is metastable and the other is stable.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…We do not solve the time-dependent Ginzburg-Landau (TDGL) equation directly. Instead, we use the cell dynamics method 29 to solve TDGL approximately. In a previous study we 20,30 have already shown that the cell dynamics method is accurate enough and numerically very efficient to study the general feature of the dynamics of various first order phase transformations.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…Although their degrees of simplification of the dynamics differ, it is often the case that discretization for pattern generation is discussed under the same framework [2]. One of the models that rather faithfully discretizes the dynamics of a continuous system is that of Markus and Hess [3] which uses a complex rule configuration.…”
Section: Modelmentioning
confidence: 99%